Enhancing the Performance of Crime Prediction Technique Using Data Mining - P.Raja Rajeswari, Dr; Surya Teja, P; Sri Harsha, P; Chaitanya Kumar, T (International Journal of Engineering and Technology, 2018)
Time is a important factor for criminal sentencing. Most of the times, criminal released on the bail which may harmful to the society, even after they have furnished the judgment. This sort of threats cut down through the prediction analysis. The analysis can be done on the concerned person to analyse that she/ he is about to do the crime. So that, its benefit not only for law enforcement but also for country safety. Data Mining, a method which handles a massive datasets. Data mining also used to guess desired patterns. Police Officers are the best persons for crime prediction and also predict the criminalâ€™s upcoming activities. We are here implementing the use of Frequent Mining Pattern in addition to Association Rule Mining. The main aim of this paper is analysing several crimes by various criminals and to predict chance of crimes by same criminal. It will be helpful for Country Law Enforcement and safeguarding from criminals who were released on Bail. Aim can be achieved with the help of Apriori Algorithm.Â Â